Zambia, Mining, and Neoliberalism
XXI, 298 p. 6 illus.
Keywords: This book paints a vivid picture of Zambia's experience riding the copper price rollercoaster. It brings together the best of recent research on Zambia's mining industry from eminent scholars in history, geography, anthropology, politics, sociology and economics. The authors discuss how aid donors pressed Zambia to privatize its key industry and how multinational mining houses took advantage of tax-breaks and lax regulation. It considers the opportunities and dangers presented by Chinese investment, how both companies and the Zambian state responded to dramatic instabilities in global commodity markets since 2004, and how frustration with the courting of mining multinationals has led to the rise of populist opposition. This detailed study of a key industry in a poor Central African state tells us a great deal about the unstable nature and uneven impacts of the whole global economic system.